2014
DOI: 10.5070/v426110332
|View full text |Cite
|
Sign up to set email alerts
|

Development of Re-Setting Toxin Delivery Devices and Long-Life Lures for Rats

Abstract: Introduced rats continue to have a major impact on biodiversity around the world, and improved control techniques are required to avoid further extinctions. We are trialing re-setting toxin-delivery systems (Spitfires) targeting a range of predators, including rats. The rat Spitfire works by firing 800 mg of a toxic paste onto the belly of the rat as it passes through a tunnel; the device then resets. When the rats groom the paste from their fur, they ingest the toxin. Each Spitfire is capable of approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Stoats are notoriously difficult to detect and control, requiring a range of techniques (Dilks et al 1996;Murphy et al 2014;Smith & Weston 2017). Stoats are known to have individual dietary preferences (Murphy & Dowding 1994;Smith et al 2008), and thus a range of options for toxic baits is also required.…”
Section: Discussionmentioning
confidence: 99%
“…Stoats are notoriously difficult to detect and control, requiring a range of techniques (Dilks et al 1996;Murphy et al 2014;Smith & Weston 2017). Stoats are known to have individual dietary preferences (Murphy & Dowding 1994;Smith et al 2008), and thus a range of options for toxic baits is also required.…”
Section: Discussionmentioning
confidence: 99%
“…For the long-term control of rats, a range of tools with different modes of action will be required (Campbell et al 2015). Resetting toxin devices (Spitfires) have been explored for the control of rats, stoats (Mustela erminea), and brushtail possums (Trichosurus vulpecula) in New Zealand (Murphy et al 2014(Murphy et al , 2018Blackie et al 2016). The Spitfire works by firing a paste containing a toxin onto the ventral surface of a pest and the device then re-sets.…”
Section: Introductionmentioning
confidence: 99%
“…Martin [24] found that reduced activity rates of stoats in early summer made tracking tunnel monitoring less effective, so this may be a time when more attractive lures could increase control and monitoring efficacy. Recent innovations such as tunnels that squirt toxins onto body fur [25] and 'virtual barriers' [26] could also benefit from effective long-life species-specific lures.…”
Section: Introductionmentioning
confidence: 99%